High-circulating Tie2 Is Associated With Pathologic Complete Response to Chemotherapy and Antiangiogenic Therapy in Breast Cancer. (June 2016) - Makhoul, Issam; Griffin, Robert J.; Siegel, Eric; Lee, Jeannette; Dhakal, Ishwori; Raj, Vinay; Jamshidi-Parsian, Azemat; Klimberg, Suzanne; Hutchins, Laura F.; Kadlubar, Susan
Abstract : Introduction: Vascular endothelial growth factor (VEGF) is a central mediator of angiogenesis in breast cancer. Research in antiangiogenic cancer treatment has been marked by the development of the monoclonal antibody bevacizumab, which targets VEGF in many solid tumors. As patients do not equally benefit from bevacizumab, it has become necessary to define the profile of patients who will benefit from the drug. Materials and Methods: We have conducted a prospective phase II study in 39 patients using bevacizumab in breast cancer in the neoadjuvant setting, and found improved pathologic complete response (pCR) when bevacizumab was added to chemotherapy in patients with hormone receptor negative and invasive ductal carcinoma. Blood samples were collected at baseline and serially while patients were on treatment. Circulating angiogenesis-related proteins angiopoietin (ANG)1, ANG2, basic fibroblast growth factor, IL-1a, matrix metalloproteinase 9, platelet derived growth factor - BB, platelet endothelial cell adhesion molecule -1, Tie2, VEGF, and vascular endothelial growth factor receptor 2 were measured at baseline and during treatment. This correlative study was conducted to identify specific serum angiogenic factor profiles that might be associated with pCR in the neoadjuvant setting in breast cancer patients receiving bevacizumab and chemotherapy. Results: Elevated baseline serum Tie2 and basic fibroblast growth factor were associated with pCR in response to this combination. Changes in serum levels of these proteins were seen during treatment but were not significantly different between the pCR and non-pCR groups. Conclusions: Baseline-circulating Tie2 levels may help distinguish patients who will have pCR from those who will not and may form the basis for future development of antiangiogenic therapy in breast cancer. Larger studies are needed to validate these findings. ClinicalTrials.gov Identifier: NCT00203502.